FASILITASI SEKRETARIAT DPRD DIY DALAM RAPAT PEMBAHASAN LAPORAN KETERANGAN PERTANGGUNGJAWABAN GUBERNUR TAHUN ANGGARAN 2013 - , FEBRINA DWI F R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The theme of the event this Internship Parliament Secretariat is facilitating natural DIY Discussion Meeting Consolidated Statement Accountability Governors Fiscal Year 2013. The reason for the discussion is carried out between the Executive Members of the Legislative Council Secretariat DIY . The object of this understand the process of DIY Government in allocating funds for 1 ( one ) year kpada community in order to prosper the community . The purpose of the this internship , the first , is one of the graduation requirements of D3 Law Program . Second , to determine the duties and functions of the Parliament Secretariat DIY . Third , to know the activities of the Parliament Secretariat DIY . As for the benefits of the Field Work Practice Activities , first , to add to the experience in the world of work . Second , to create a responsibility to complete a job . Third , to train of thinking in solving problems. In the Parliament Secretariat is basic organizational structure that is part Hearings , Legislation Section , General Section , and the Finance Department . In addition , there are also some of the Board Members of each faction formed the Special Committee meeting to discuss the duties performed in the Parliament Secretariat DIY . In facilitating the meeting there , every parts in DIY Parliament Secretariat have their respective duties and obligations different .